Case Study : Al-Ikhsan Sports / Ahmad Khuzairi Rusydi Ahmad Iskandar - Ahmad Iskandar, Ahmad Khuzairi Rusydi (2021)
Al-Ikhsan Sports Sdn Bhd is Malaysia’s No. 1 sports retailer which is primarily involved in the retail of sports footwear, apparel and equipment. Al-Ikhsan Sports was established in 1993 with a single 150sqft store in Holiday Plaza, Johor Bahru by a husband and wife team, Tuan Haji Ali Hassan and Pn Marina Abu Bakar. From a sole proprietorship enterprise, the Company has evolved to a Private Limited Company now known as Al-Ikhsan Sports Sdn Bhd. The business has grown tremendously and currently has over 125 stores located throughout Peninsular Malaysia. Since its inception, the company has grown from a singular sports convenience concept to a multi-category, multi-concept sporting goods giant with a clearly segmented strategy to address consumers and sports lover across different income groups, offering global brands at affordable price.